Gene mutations associated with fertilization failure after in vitro fertilization/intracytoplasmic sperm injection - Xue, Yamei; Cheng, Xiaohong; Xiong, Yuping; Li, Kun (Frontiers in Endocrinology, 2022)
Fertilization failure during assisted reproductive technologies (ART) is often unpredictable, as this failure is encountered only after in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) have been performed. The etiology of fertilization failure remains elusive. More and more mutations of genes are found to be involved in human fertilization failure in infertile patients as high throughput sequencing techniques are becoming widely applied. In this review, the mutations of nine important genes expressed in sperm or oocytes, PLCZ1, ACTL7A, ACTL9, DNAH17, WEE2, TUBB8, NLRP5, ZP2, and TLE6, were summarized and discussed. These abnormalities mainly have shown Mendelian patterns of inheritance, including dominant and recessive inheritance, although de novo mutations were present in some cases. The review revealed the crucial roles of each reported gene in the fertilization process and summarized all known mutations and their corresponding phenotypes. The review suggested the mutations might become promising targets for precision treatments in reproductive medicine. Moreover, our work will provide some helpful clues for genetic counseling, risk prediction, and optimizing clinical treatments for human infertility by supplying the useful and timely information on the genetic causes leading to fertilization failure.